Hepatoblastoma: A Need for Cell Lines and Tissue Banks to Develop Targeted Drug Therapies - Rikhi, Rishi Raj; Spady, Kimberlee K.; Hoffman, Ruth I.; Bateman, Michael S.; Bateman, Max; Howard, Lisa Easom (Frontiers in Pediatrics, 2016)
Limited research exists regarding the most aggressive forms of hepatoblastoma. Cell lines of the rare subtypes of hepatoblastoma with poor prognosis are not only difficult to attain, but are challenging to characterize histologically. A community approach to educating parents and families of the need for donated tissue is necessary for scientists to have access to resources for murine models and drug discovery. Herein we describe the currently available resources, the today’s existing gaps in research, and the path to move forward for uniform cure of hepatoblastoma.